USE OF GLP-1 RECEPTOR AGONISTS AND/OR SGLT-2 INHIBITORS AMONG PATIENTS WITH PERIPHERAL ARTERY DISEASE BEFORE AND AFTER REVASCULARIZATION IN A SINGLE-CENTER COHORT - Franck H. Azobou Tonleu, MD (Elsevier, 2024)
Therapeutic Area: Peripheral Artery Disease Background: Diabetes mellitus (DM) is a major risk factor for peripheral artery disease (PAD). Patients with both PAD and DM have an increased risk of major adverse atherosclerotic events. GLP-1 RA and SGLT-2i are recommended to improve major adverse cardiac events among patients with atherosclerotic disease. Despite this, optimal treatment remains an unmet need. Methods: The cohort included patients who have undergone their index limb revascularization for PAD between 01/01/2021 and 12/31/2022 at a major urban safety net hospital. The cohort was created using ICD-10 and CPT codes. The cohort was created using ICD-10 and CPT codes. GLP-1 RA and SGLT-2i prescriptions and HbA1c were abstracted at baseline (prior to index revascularization) and at 1 year post discharge. Results: The final cohort included 311 patients with 36% female, 49% Hispanic, 36% Black, and was 63 ± 10 years old. Furthermore, 58% were either on Medicaid or a hospital-specific subsidized health plan. History of hypertension, hyperlipidemia, and type 2 diabetes were seen in 98%, 93%, and 79% of patients, respectively. Of the 288 patients with A1c prior or during revascularization, median was 7.55% and 45% (129/288) had HA1C < 7%. Only 176 (57%) patients had HA1C check within 1 year of revascularization with median 7.33% and 44% (77/176) with HA1C < 7%. Looking at diabetes medications, the number of patients on GLP-1 RA increased from 27 (9%) to 53 (17%). The number of patients on SGLT-2i increased from 55 (18%) to 82 (26%), and that of metformin increased from 172 (55%) to 191 (61%). Conclusions: In a large safety net hospital with high rates of comorbid diabetes and peripheral artery disease, only 176 (57%) patients had repeat HA1C within 1 year of revascularization. Despite an increase in metformin, GLP-1 RA, SGLT-2i use, the glycemic control remained poor with only 1 in 4 patients with documented to be at HbA1c <7% at 1 year. These findings highlight an important care gap, and revascularization as an important opportunity for medical optimization. Clinician education and EHR (electronic health record) interventions could be leveraged to improve outcomes in this population.